2016
DOI: 10.4049/jimmunol.1502465
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Commensal Microbiota Has Disparate Effects on Manifestations of Polyglandular Autoimmune Inflammation

Abstract: Polyglandular autoimmune inflammation accompanies Type 1 diabetes (T1D) in NOD mice affecting organs like thyroid and salivary glands. Whereas commensals are not required for T1D progression, germ-free (GF) mice had a very low degree of sialitis, which was restored by colonization with select microbial lineages. Moreover, unlike T1D, which is blocked in mice lacking MyD88-signaling adaptor under conventional but not under GF housing conditions, sialitis did not develop in MyD88-negative GF mice. Thus, microbes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
5
22
0
2
Order By: Relevance
“…Here, we demonstrate that the prebiotic compound XOS can change the gut microbiota and delay the onset of type 1 diabetes in NOD mice and reduce autoimmune cellular reactions against pancreatic beta cells and salivary glands. This is in line with previous results demonstrating that a variety of intestinal bacteria can regulate the degree of both insulitis and sialadenitis in NOD mice [16,28,29]. The high degree of insulitis in antibiotic-treated mice resembles that observed in germ-free NOD mice [29].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Here, we demonstrate that the prebiotic compound XOS can change the gut microbiota and delay the onset of type 1 diabetes in NOD mice and reduce autoimmune cellular reactions against pancreatic beta cells and salivary glands. This is in line with previous results demonstrating that a variety of intestinal bacteria can regulate the degree of both insulitis and sialadenitis in NOD mice [16,28,29]. The high degree of insulitis in antibiotic-treated mice resembles that observed in germ-free NOD mice [29].…”
Section: Discussionsupporting
confidence: 92%
“…It is worth considering that in such a scenario, without XOS as an available nutrient source, the microbiota may function differently and, therefore, a microbiotamediated anti-inflammatory effect of an XOS-supplemented diet should therefore not be ruled out. In contrast to the effect on insulitis, the development of sialadenitis was clearly regulated by gut bacteria, which is comparable with our previous study in germ-free mice [16]. These findings warrant further investigation into the regulatory role of Parabacteroides spp.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies in NOD mice had shown that altering female sex hormones through castration did not modulate the development of sialadenitis in females, whereas castration of males increased development of sialadenitis (Fig. c) . Similar proportions of Treg cells were observed in castrated and sham‐castrated mice, indicating that this effect was not the result of differences in the frequency of Treg cells in the absence of testosterone (Fig.…”
Section: Resultssupporting
confidence: 51%
“…Дисбактеріоз/дисбіоз, сформу-вавшись як супутній стан, може призвести до низ-ки ускладнень, що негативно впливають на перебіг основного захворювання. Саме дисбактеріоз може ставати провідним захворюванням -інфекційним процесом змішаної етіології [19].…”
Section: № 5 2017unclassified